Meta-cognitive Strategies in College Students’ WeChat Mobile EnglishLearning - Li, Zhanfang; Peng, Mengying (Advances in Social Sciences Research Journal, 2019)
The development of the Internet information technology and the popularization of mobile devices have brought about a new paradigm of learning, Mobile Learning, which is becoming increasingly common in the college English learning. In addition, as a multifunctional messaging and social media application attached to mobile devices, WeChat has enjoyed great popularity among college students and teachers and has been considered as a useful mobile English learning tool, because of its convenient method of operation and its unique features of sending and sharing texts, voices, pictures, videos, web links and so forth. However, the numerous potential distractions have also turned WeChat platform into a double-edged sword for college students when it comes to self-regulated learning. This study investigates the situation of college students’ mobile English learning based on WeChat from the perspective of meta-cognitive strategies, which include self-planning, self-monitoring and self-evaluating through questionnaire. Figuring out the current situation of the mobile college students’ English learning based on WeChat, this study finds that the college teachers’ and students’ knowledge of this new paradigm of learning and their awareness of how to apply it are still insufficient. Besides, the levels of students’ using meta-cognitive strategies are generally not high enough, and students’ gender and major also have an influence on the levels of the three meta-cognitive strategies.